Malaria - Kasenga, Fyson H. (Infectious Diseases, 2019)
Each year, malaria kills almost half a million people despite the fact that it is a preventable and curable disease. Malaria has a direct correlation with economic loss due to the need for people to take time off work and the cost of hospital treatments. Undertaking decisive measures to combat malaria is necessary. This book aims to present current approaches in the treatment of malaria. It will be a guide to those working in malaria-endemic regions and cover both diagnosis and treatment. It will also be useful for medical workers in western countries where malaria is not as common. Considering that malaria causes morbidity and mortality, more especially among children below five years of age and pregnant mothers, it is therefore imperative that people from all walks of life should join hands to address this public health problem.